RESEÑA de: Mirizio, Annalisa (ed.). Fuera del cuadro: cine, palabra e imagen en las artes modernas. Madrid: Pigmalión Edipro, 2014 - López López, Carmen María (Signa: Revista de la Asociación Española de Semiótica, 2016)
-